On the Global Well-Posedness of the Viscous Two-Component Camassa-Holm System - Xiuming Li (Abstract and Applied Analysis)
We establish the local well-posedness for the viscous two-component Camassa-Holm system. Moreover, applying the energy identity, we obtain a global existence result for the system with (u0,η0)∈H1(ℝ)×L2(ℝ).